2023
DOI: 10.3390/biom13020353
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and NRF2 Signaling, Friends or Foes in Cancer?

Abstract: The imbalance between reactive oxygen species (ROS) production and clearance causes oxidative stress and ROS, which play a central role in regulating cell and tissue physiology and pathology. Contingent upon concentration, ROS influence cancer development in contradictory ways, either stimulating cancer survival and growth or causing cell death. Cells developed evolutionarily conserved programs to sense and adapt redox the fluctuations to regulate ROS as either signaling molecules or toxic insults. The transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 122 publications
0
19
0
Order By: Relevance
“…The O 2 − generated in the mitochondria reacts with mnSOD in the mitochondrial matrix to produce H 2 O 2 , which in turn can cross the mitochondrial outer membrane and reach the cytosolic targets. The H 2 O 2 assault on the cytosolic targets can cause numerous deleterious functional consequences such as stimulation of redox-sensitive transcription factors, proinflammatory cytokines, and inflammasomes [ 101 , 102 , 103 ]. mtROS can also contribute to increased oxidative stress through interactions with NOS [ 87 ].…”
Section: Sepsis-induced Aki (Saki)mentioning
confidence: 99%
“…The O 2 − generated in the mitochondria reacts with mnSOD in the mitochondrial matrix to produce H 2 O 2 , which in turn can cross the mitochondrial outer membrane and reach the cytosolic targets. The H 2 O 2 assault on the cytosolic targets can cause numerous deleterious functional consequences such as stimulation of redox-sensitive transcription factors, proinflammatory cytokines, and inflammasomes [ 101 , 102 , 103 ]. mtROS can also contribute to increased oxidative stress through interactions with NOS [ 87 ].…”
Section: Sepsis-induced Aki (Saki)mentioning
confidence: 99%
“…Upon exposure to sunlight, endogenous chromophores present in the skin initiate the conversion of sunlight photons to ROS. Although ROS have important physiological functions in cell signaling, enzymatic reactions, and resistance against microbes, their excessive levels can be toxic unless they are removed in a timely manner ( Wang et al ., 2023 ). As keratinocytes form the outermost layer of the skin and are frequently exposed to stressful stimuli, sophisticated cyto-protective functions likely play an important role in maintaining their proper functions in this tissue.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of evidence has proved that tobacco smoke contains over 3500 chemicals and 60 carcinogens, which include but are not limited to volatile organic hydrocarbons, polycyclic aromatic hydrocarbons, and N -Nitrosamines [ 17 ]. Moreover, some of the chemicals in tobacco smoke are considered to be reactive oxygen species (ROS), which can promote inflammation and mediate processes such as cell proliferation, cell cycle progression, and metastasis [ 17 , 18 ]. Accordingly, data have demonstrated that the byproducts of the chemicals and compounds in tobacco smoke are found in the urine of smokers at higher levels than that of non-smokers.…”
Section: Introductionmentioning
confidence: 99%